Aspectos celulares e bioquímicos do mecanismo de ação do antidepressivo clomipramina em protozoários tripanosomatídeos - Rodrigues, Jean Henrique da Silva (2017)
Tropical Neglected Diseases (TNDs) are a group of severe disabling conditions characterized by their social and economic impacts, and by affecting mainly people in the poorest countries. Despite their important morbidity and mortality rates, historically the TNDs have not been subject of appropriate studies in the search and development of new drugs, possibly due to the restrict profit expected. Among the TNDs the parasitic diseases caused by protozoa belonging to order Kinetoplastida are known by affecting millions of people and animals all over the world. The most important etiological agents in this group are protozoa from genera Leishmania, which cause a broad range of diseases in the tropics and subtropics called leishmaniasis, and Trypanosoma, that includes causative agents of human trypanosomiasis. In sub-Saharan Africa, Trypanosoma brucei is responsible for causing sleeping sickness, and in Latin America, Trypanosoma cruzi causes Chagas' disease. Treatment for these diseases remains a problem, since vaccines are not available and chemotherapy is restricted to only a few drugs with limited efficacy. On the pursuit of novel therapeutic alternatives for NTD, drug repurposing arises as a faster and cheaper approach. Also known as drug repositioning, it consists on the identification of new uses for medicaments originally approved for a different purpose. Based on that strategy, miltefosine and amphotericin B, drugs respectively conceived and anti-cancer and anti-fungus agents where later repurposed for the treatment of leishmaniasis. Clomipramine, a drug initially conceived as an anti-depressant and currently used in the treatment of Obsessive Compulsive Disorder was found to be an efficient inhibitor of trypanothione reductase (TR) with promising use on Chagas disease. Considering that TR is an exclusive and essential enzyme on the antioxidant metabolism of trypanosomes, the present work evaluates the repurposing of the antidepressant clomipramine (clomi) for the treatment of leishmaniasis and Human African Trypanosomiasis (HAT), as well the ultrastructural and biochemical alterations involved on the mechanism of action of the drug on the parasites. The potential of clomi was evaluated in vitro against two species of flagellate protozoa: Trypanosoma brucei brucei (EATRO 427 MITat 1.2 strain), maintained in HMI-9 medium at 37 °C and 5% CO2, and Leishmania amazonensis (WHOM/BR/75/JOSEFA strain), cultivated in Warren medium at 25 °C. The antiproliferative activity of clomi was assessed against bloodstream forms of T. brucei, using both direct counting and phosphatase activity as a viability sensor. The inhibitory activity against L. amazonensis promastigotes was assessed by the tetrazolium salt XTT. The activity against intracellular amastigotes was evaluated in J774A.1 macrophages infected with L. amazonensis promastigotes. The safety of clomi against mammal cells was determined in J774A.1 macrophages by MTT reduction assay. The mechanism of action of clomi was determined in extracellular parasites incubated with the IC50 for at least 24 h. In order to analyze the effect in L. amazonensis intracellular amastigotes, infected macrophages were also treated for 24 h with IC50 and IC90, afterwards parasites were isolated through host cell disruption and differential centrifugation. The ultrastructural and morphological alterations in clomi-treated parasites were observed by transmission and scanning electron microscopy. Cell parameters related to energetic metabolism, membrane integrity, cell cycle, plus the occurrence of apoptosis and autophagy were also analyzed in clomi-treated parasites, by using sort of different techniques, including flow cytometry, spectrophotometry and fluorimetry. Our results showed the inhibitory potency of clomi against the causative agents of leishmaniasis and HAT, presenting inhibitory concentrations for 50% (IC50) of cell growth/viability equal to 5.4 ± 0.23 µM (at 24 h), 8.31 ± 3.29 µM (at 72 h) and 15.45 ± 4.92 µM (at 48 h), respectively for T. brucei bloodstream forms, promastigotes and amastigotes of L. amazonensis. Besides its wide use in the clinics, the safety of the drug was also assured by low cytotoxicity against host macrophages (CC50: 181.22 ± 8.04 µM), what indicates the selective activity of clomi against the parasites. In terms of cellular targets of clomi action, our findings clearly indicates deep mitochondrial involvement. The mitochondrial membrane potential depolarization seems to be a primordial step of the mechanism of action in both parasites. Together with the inhibition of TR, an enzyme involved on the recycling of the antioxidant trypanothione, the impairment of mitochondrial potential led to ROS accumulation and end up in intense oxidative stress. Additional direct interaction between clomipramine and the parasite DNA has also been detect in T. brucei. Among several consequences, the oxidative stress in promastigotes was evidenced as intense lipoperoxidation, accumulation of lipid droplets and disruption of cell membrane, all effects at least partially inhibited when cells were pre-treated with the antioxidant n-acetylcysteine. Interestingly, neither lipoperoxidation nor cell membrane disruption were observed in intracellular amastigotes, possibly due to the stress metabolic resistance innate of this parasitic stage. Another important metabolic difference was observed by analyzing the ATP levels, which were reduced in amastigotes but kept constant in promastigotes, although the mitochondrial depolarization induced by clomi. In attempt to get homeostasis back cell makes use of recovery pathways, with remarked autophagy observed in both parasites. Interestingly, in T. brucei when wortmannin (autophagy inhibitor) has been simultaneously applied with clomi an increase in the inhibitory activity has been observed, possibly indicating its saving role. As an additional adaptive response the exacerbation of exocytosis was also detected in clomi-treated L. amazonensis. The unsuccessfully effort to recover cell homeostasis terminates contributing to cell demise. Later effects observed in treated parasites includes typical features of programmed cell death (i.e. DNA fragmentation, phosphatidylserine exposition, cell shrinking and caspase-like activity) suggesting death by an apoptosis-like pathway.Taken together our results supports further studies on the repurposing of Clomipramine on the treatment of leishmaniasis and HAT. The antidepressant selectively acts on L. amazonensis and T. brucei by a mitochondrial pathway mostly, inducing severe oxidative stress and, despite the adaptive responses of autophagy and activated exocytosis, parasites end up dying through an apoptosis-like programmed cell death.